Kidneys from Older Living Donors Provide Excellent Short and Intermediate Outcomes—A Single China Center's Experience. Issue 8 (August 2015) - Song, Turun; Fu, Lei; Rao, Zhengsheng; Zeng, Dongyang; Huang, Zhongli; Wang, Xianding; Chen, Mianzhi; Wei, Qiang; Lin, Tao
<x xml:space="preserve">Abstract</x> Background Transplantation with kidneys from older living donors is on the rise, yet controversy still exists over whether the outcomes are as satisfactory as with kidneys from younger donors. Methods We retrospectively analyzed 1009 living donor kidney transplants performed at our center between 2006 and 2013. Graft and patient outcomes were compared between transplants with kidneys from old living donors (OLD, 55-65 years) (n = 264) and from young living donors (YLD, <55 years) (n = 745). Results The age was 32.80 ± 9.71 years and 33.91 ± 5.98 years for recipient in YLD and OLD group, respectively. Death-censored graft survival at 1, 3, and 5 years was 98.8%, 97.1%, and 95.8% in patients receiving YLD kidneys, similar to the corresponding values of 97.6%, 95.5% and 95.5% in patients receiving OLD kidneys (P = 0.356). Patient survival at 1, 3, and 5 years after transplantation was also similar for patients receiving YLD kidneys (98.5%, 97.1%, and 96.7%) and for patients receiving OLD kidneys (99.6%, 99.6%, and 96.8%; P = 0.110). The OLD kidneys were not associated with increased risk of death-censored graft failure (hazard ratio, 2.5; 95% confidence interval, 0.57 to 11.11) and patient death (hazard ratio, 1.67; 95% confidence interval, 0.75 to 3.73). In addition, there is no increased graft loss or patient death for each 10-year increase in donor age. Transplantation with OLD kidneys was not associated with reduced patient or graft outcomes in the short term (⩽12 months) or medium term (>1 year). Conclusions Graft and patient outcomes after living-donor kidney transplantation are similar in the short-term and medium-term for donors aged 55 to 65 years and for younger donors. Therefore, the use of OLD kidneys should be encouraged in China.